Hubungan Faktor-faktor yang Memengaruhi Kepatuhan Minum Obat dengan Kepatuhan Pasien Skizofrenia yang Mengalami Halusinasi di RS Husada - Setyaningsih, Tri; Fitria, Dian; supriyanah, Supriyanah (Jurnal Kesehatan Holistic, 2018)
Schizophrenia is a chronic mental disorder that causes the sufferer to experience delusions, hallucinations, chaotic thoughts, and behavioral changes. This study was conducted to determine the relationship of the description of the factors that influence the adherence of medication to the compliance of schizophrenic patients who experienced hallucinations in Husada Hospital. This research uses correlative descriptive method. The population in this study were all schizophrenic patients who were treated in Nusa Indah Room RS Husada. Sample in this research counted 24 people with accidental sampling sampling technique. The results of the study showed that there was a significant correlation between family support for medication adherence (p value 0,005), behavior toward drug adherence (p value 0,006), economic level of drug adherence compliance (p value 0,005), education level to medication adherence p value 0.031), knowledge of medication adherence (p value 0.035) and social support for medication adherence (p value 0.037).